1975
DOI: 10.1073/pnas.72.2.733
|View full text |Cite
|
Sign up to set email alerts
|

Preferential and cooperative binding of histone I to chromosomal mammalian DNA.

Abstract: There is a strong preferential binding of histone I to lymphocyte DNA as compared to Escherichia coli DNA when large DNA fragments (2 X 106 daltons) are used. The binding of histone I to lymphocyte DNA and to E. coli DNA is cooperative. The distribution of preferential binding sites has been investigated on fragmented DNA. Most of the 2 X 106 dalton fragments were found to have at least one preferential histone I binding site, whereas most of the 2 X 106 dalton fragments have none.Specific DNA-protein interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The preference of histone H1 for a subfraction of the mammalian genomic DNA [Renz, 1975;Diez-Caballero et al, 19891 and even to a discrete region flanking the rat albumin gene has been reported earlier [Sevall, 19881. It has been even suggested that dispersed preferential binding sites for H1 exist in the mammalian genome [Renz, 1975;Diez-Caballero et al, 19891. This speculation is particularly interesting in view of the suggestion that SARs may control the conformation of chromatin domains through their highly specific association with H1 [Izaurralde et al, 19891. In the latter case the specificity of the interaction was demonstrated by the formation of specific precipitable complexes between isolated histone H1 and several SARs.…”
Section: Discussionmentioning
confidence: 84%
“…The preference of histone H1 for a subfraction of the mammalian genomic DNA [Renz, 1975;Diez-Caballero et al, 19891 and even to a discrete region flanking the rat albumin gene has been reported earlier [Sevall, 19881. It has been even suggested that dispersed preferential binding sites for H1 exist in the mammalian genome [Renz, 1975;Diez-Caballero et al, 19891. This speculation is particularly interesting in view of the suggestion that SARs may control the conformation of chromatin domains through their highly specific association with H1 [Izaurralde et al, 19891. In the latter case the specificity of the interaction was demonstrated by the formation of specific precipitable complexes between isolated histone H1 and several SARs.…”
Section: Discussionmentioning
confidence: 84%
“…It has long been known that H1 histone binds preferentially to AT-rich DNA (Renz, 1975). Later work in Laemmli's group showed that H1 binds cooperatively to MAR elements to nucleate further assembly of H1 molecules and condensation of chromatin Käs et al, 1989).…”
Section: The Chromatin Opening Modelmentioning
confidence: 99%
“…It has not been adequately explained, however, how a localized activation event could prevent or alter the presumed default packaging of large stretches of DNA into inactive chromatin or, alternatively, how an active chromatin structure could propagate over a large distance. Thus, the tight binding of activator proteins to their recognition sites on DNA would be expected to generate nucleosome-free DNase-hypersensitive sites in that region, as observed (16), but the concomitant opening of a large adjacent chromatin domain would not be expected, given the known physical chemistry of histone-DNA interactions.It has been suggested that the breaking of cooperative interactions among histone Hi molecules in chromatin at a hypersensitive site might lead to the destabilization (and potential activation) of a large region of chromatin (50).However, although histone Hi binds cooperatively to naked DNA (11,25,35) been demonstrated, and highly cooperative binding appears unlikely (1). Moreover, active chicken ,-globin chromatin from erythroid nuclei exists in a compacted state, consistent with either a fully folded 30-nm fiber containing a local disruption at the nucleosome-free hypersensitive region (5) or an only slightly disrupted fiber (19).…”
mentioning
confidence: 99%
“…However, although histone Hi binds cooperatively to naked DNA (11,25,35) been demonstrated, and highly cooperative binding appears unlikely (1). Moreover, active chicken ,-globin chromatin from erythroid nuclei exists in a compacted state, consistent with either a fully folded 30-nm fiber containing a local disruption at the nucleosome-free hypersensitive region (5) or an only slightly disrupted fiber (19).…”
mentioning
confidence: 99%